2021
DOI: 10.3390/ani11051418
|View full text |Cite
|
Sign up to set email alerts
|

Canine Placenta Histological Findings and Microvascular Density: The Histological Basis of a Negative Neonatal Outcome?

Abstract: Placenta is essential for the development of the fetus, and its impaired function can lead to a negative outcome (i.e., neonatal mortality). In dogs, investigations on placenta histology and neonatal outcome in healthy bitches are lacking, and a contribution is provided in this study to emphasize the use of placenta histology in practice. Fifty-one placentas from 11 litters were collected during cesarean section, classified according to the litter size (large (L) or small (S)) and the outcome, this latter as h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…The increased vascularization in the gravid horn might have been a compensatory feature to provide the appropriate nutrition to the equine fetus. In the bitch, the lowest ratio of placenta weight and puppy weight occurs in larger litters and when placentas depict the highest capillary density, with respect to smaller litters ( 14 ). In older mares, the highest ratio of placenta weight and foal weight was associated with more parturitions, and placentas that presented the highest vascular density, which might show an adaptation of the placenta and increased efficiency with parity, as referred ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The increased vascularization in the gravid horn might have been a compensatory feature to provide the appropriate nutrition to the equine fetus. In the bitch, the lowest ratio of placenta weight and puppy weight occurs in larger litters and when placentas depict the highest capillary density, with respect to smaller litters ( 14 ). In older mares, the highest ratio of placenta weight and foal weight was associated with more parturitions, and placentas that presented the highest vascular density, which might show an adaptation of the placenta and increased efficiency with parity, as referred ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that intrauterine fetal nutrition influences both foal's health (7,8), and its athletic performance (9,10). Nevertheless, regardless of the animal species, the macroscopic examination of the placenta does not reveal microscopic lesions that are only detected by histological examination or electron microscopy observation, and that might be related to fetal death, neonate low body weight or sickness (11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have been carried out on human and other animal species that provide information on the relation between the birth weight and placenta [ 117 , 118 , 119 , 120 , 121 ]. Several studies were conducted on dogs [ 113 , 122 ]. In small and toy breeds, authors revealed a positive correlation between the birth weight of a puppy and the placental weight and its total area [ 113 ].…”
Section: Newborn’s Related Factorsmentioning
confidence: 99%